Il territorio, il codice, la rappresentazione Il disegno dello statuto dei luoghi - Lucchesi, Fabio (Scuole di dottorato, 2005)
What are the cognitive and expressive choices involved in the concrete practices of creation of graphical representations of the territory? And what is the effectiveness of graphics in the government of the territory and its changes? These questions are the basis of the preparation of this work. The essay proposes and tests a hypothesis of representation of the "statute of places", that is, of an instrument regulating the transformations of the city and of the territory based on the recognition of common values, a little binding, but indicative for the determination of plans and projects.